1978
DOI: 10.1002/dev.420110305
|View full text |Cite
|
Sign up to set email alerts
|

Brief periods of socialization and later behavior in the rat

Abstract: Juvenile rats were allowed short daily periods of social contact to see if this would reduce the known effects of isolation rearing upon habituation of locomotor activity and object contact in the open field. Animals totally deprived of social experience (ISOL) were slower to habituate than animals living in small social groups (SOC). Rats allowed 1 hr of social contact (partial isolates, PI), but living otherwise in isolation, were intermediate between ISOL and SOC animals. In further experiments the quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
116
1
1

Year Published

1993
1993
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(124 citation statements)
references
References 18 publications
(18 reference statements)
5
116
1
1
Order By: Relevance
“…Indeed, not only are hypotheses non-mutually exclusive, play may have different functions at different parts of an animal's life [8]. A fundamental and ethical challenge in studying play is that it is difficult to deprive animals only of play (but see [10,11]) and that deprivation of play typically impedes normal development [12,13]. Thus, we must often accept correlative support for hypotheses.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, not only are hypotheses non-mutually exclusive, play may have different functions at different parts of an animal's life [8]. A fundamental and ethical challenge in studying play is that it is difficult to deprive animals only of play (but see [10,11]) and that deprivation of play typically impedes normal development [12,13]. Thus, we must often accept correlative support for hypotheses.…”
Section: Introductionmentioning
confidence: 99%
“…Social play in adolescent rats is thought to serve an essential role in fostering healthy development (Einon et al, 1978;Meaney & Stewart, 1979;Van den Berg, Hol, et al, 1999;Vanderschuren et al, 1997). Numerous studies suggest that nature has imbued the opportunity to engage in social play with intrinsic natural reward.…”
Section: Introductionmentioning
confidence: 99%
“…In rats, it has also been observed that even a short period of isolation increases the frequenc y of play fighting (Panksepp , 1981;Thor & Holloway , 1984). The locomotor hyperactivity , previously demonstrated in isolated rats (Einon, Morgan , & Kibbler , 1978), could also account for these results-greater locomotion would bring these animals into contact more frequently, resulting in a higber rate of play fighting. In accordance with Scott's (1966) and Einon & Morgan's (1977) suggestions, isolation during critical periods of socialization seems to have significant and lasting effects on aggression .…”
Section: Discussionmentioning
confidence: 88%